Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1097/00006534-199908000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Oromandibular Reconstruction with the Radial-Forearm Osteocutaneous Flap: Experience with 60 Consecutive Cases

Abstract: One of the more difficult problems in reconstructive surgery of the head and neck is replacement of bone and soft tissue lost because of injury, osteomyelitis, or malignancy. The radial-forearm osteocutaneous flap is an accepted choice for oromandibular reconstruction. This study was undertaken to review one center's experience with 60 consecutive cases of oromandibular reconstruction with the radial-forearm osteocutaneous flap. Records of the 38 men and 22 women (mean age, 60 years; range, 26 to 86 years) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 33 publications
1
64
1
3
Order By: Relevance
“…A fracture can be a significant setback for patients because it may delay recovery and rehabilitation. Operative repair is often not straightforward given the presence of skin grafts, scar and a bony defect requiring bone graft (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A fracture can be a significant setback for patients because it may delay recovery and rehabilitation. Operative repair is often not straightforward given the presence of skin grafts, scar and a bony defect requiring bone graft (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Early reports have a 15% to 30% incidence of radius fractures (19,21,22). Subsequently, biomechanical studies demonstrated the benefit of PIF (6), limiting the osteotomy to 30% of the circumference (23), and bevelling at the proximal and distal ends (13,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemos podido aprender de sus fortalezas y mejorar sus debilidades; destacando entre las ventajas más importantes el hecho de que nos permite utilizar piel, músculos, tendones, tejido adiposo, hueso y nervio según necesidad 8 , aportando piel fi na, sin pelo, de color y textura similares a la piel de la cara y el cuello 9 . El componente cutáneo del colgajo es ideal para la cobertura de mucosas, ya que con el tiempo termina modifi cando su epitelio hasta convertirse en mucosa oral y/o nasal [10][11][12][13] , se caracteriza también por ser maleable, fl exible y resistente en el tiempo 14 , no tiene contraindicaciones de edad o patologías asociadas 15 y la zona dadora mantiene su funcionalidad con un acotado compromiso estético y de baja morbilidad. La toma del colgajo es una técnica relativamente simple, se obtiene un "largo" pedículo vascular, de buen diámetro, que permite transferir tejidos a mayor distancia de la zona dadora, sin necesidad de microcirugía 2 .…”
Section: A B C D E Funclassified
“…[19][20][21] Composite RAFF which had been proposed in the earlier years has become very much less used now due to the inadequate quality and quantity of the bone available as well as the need for prolonged protection of the forearm to prevent fracture of the residual radial bone. [22][23][24] …”
Section: Choice Of Vascularized Bone Flaps and Relative Meritsmentioning
confidence: 99%